(untitled) (International journal of artificial intelligence, 2025)
This article explores the use of artificial intelligence (AI) in organizing prosecutorial supervision, emphasizing both its potential and challenges. The study highlights that AI technologies significantly enhance the efficiency, objectivity, and transparency of prosecutorial activities by enabling data-driven analysis, digital monitoring, and automated decision support. However, their integration raises a number of legal, ethical, and technical issues, including questions of legal responsibility, data protection, algorithmic transparency, and respect for human rights. The article also proposes specific legal and institutional solutions, such as the adoption of a separate law on artificial intelligence, the establishment of cybersecurity units within the prosecutor’s office, and the introduction of AI-related legal education programs. The conclusion stresses that AI should not replace human prosecutors but serve as a supportive tool that strengthens legality, fairness, and accountability within the justice system.